(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2014)
Introduction. At present there are many electrical schematic metal detectors (the most common kind of ground penetrating radar), which are differ in purpose. Each scheme has its own advantages and disadvantages compared to other schemes. Designing metal detector problem of optimal selection of functional units most schemes can only work with a narrow range of special purpose units. Functional units used in circuits can be replaced by better ones, but specialization schemes do not provide such a possibility. Description of problem. Author has created a "complex for research of functional units of metal detectors" that is the universal system that meets the task. With this set of studies conducted on the practical implementation of radar-eddy current method of distinguishing non-ferrous metals (gold, copper, etc.) is based. Description of method. Mathematical tools using have to be treated as a signal metal detector to distinguish metals: gold, copper and others. Conclusions. Processing of partial pulses may have information about beforehand signal loss during propagation in heterogeneous media with lossy nonuniform distribution parameters. Using eddy currents To calculate the value of the input voltage depending on the conductivity of the metal in the receiving antenna.Combining two different methods for processing the received signal theoretically it could be proved that with high probability can distinguish non-ferrous metals - gold, copper etc.